On the Properties of the R2 Indicator - Brockhoff, Dimo; Wagner, Tobias; Trautmann, Heike (Proceedings of the 14th Annual Conference on Genetic and Evolutionary Computation)
In multiobjective optimization, set-based performance indicators are commonly used to assess the quality of a Pareto front approximation. Based on the scalarization obtained by these indicators, a performance comparison of multiobjective optimization algorithms becomes possible. The R2 and the Hypervolume (HV) indicator represent two recommended approaches which have shown a correlated behavior in recent empirical studies. Whereas the HV indicator has been comprehensively analyzed in the last years, almost no studies on the R2 indicator exist. In this paper, we thus perform a comprehensive investigation of the properties of the R2 indicator in a theoretical and empirical way. The influence of the number and distribution of the weight vectors on the optimal distribution of μ solutions is analyzed. Based on a comparative analysis, specific characteristics and differences of the R2 and HV indicator are presented.
Keywords: hypervolume indicator; multiobjective optimization; performance assessment; r2 indicator

Algorithm Selection Based on Exploratory Landscape Analysis and Cost-Sensitive Learning - Bischl, Bernd; Mersmann, Olaf; Trautmann, Heike; Preuß, Mike (Proceedings of the 14th Annual Conference on Genetic and Evolutionary Computation)
The steady supply of new optimization methods makes the algorithm selection problem (ASP) an increasingly pressing and challenging task, specially for real-world black-box optimization problems. The introduced approach considers the ASP as a cost-sensitive classification task which is based on Exploratory Landscape Analysis. Low-level features gathered by systematic sampling of the function on the feasible set are used to predict a well-performing algorithm out of a given portfolio. Example-specific label costs are defined by the expected runtime of each candidate algorithm. We use one-sided support vector regression to solve this learning problem. The approach is illustrated by means of the optimization problems and algorithms of the BBOB’09/10 workshop.
Keywords: machine learning; exploratory landscape analysis; fitness landscape; benchmarking; evolutionary optimization; bbob test set; algorithm selection

Local Search and the Traveling Salesman Problem: A Feature-Based Characterization of Problem Hardness - Mersmann, Olaf; Bischl, Bernd; Bossek, Jakob; Trautmann, Heike; Wagner, Markus; Neumann, Frank (Learning and Intelligent Optimization)
With this paper we contribute to the understanding of the success of 2-opt based local search algorithms for solving the traveling salesman problem (TSP). Although 2-opt is widely used in practice, it is hard to understand its success from a theoretical perspective. We take a statistical approach and examine the features of TSP instances that make the problem either hard or easy to solve. As a measure of problem difficulty for 2-opt we use the approximation ratio that it achieves on a given instance. Our investigations point out important features that make TSP instances hard or easy to be approximated by 2-opt.

Resampling Methods in Model Validation - Bischl, B; Mersmann, O; Trautmann, Heike; Weihs, C (Evolutionary Computation Journal)
Meta-modeling has become a crucial tool in solving expensive optimization problems. Much of the work in the past has focused on finding a good regression method to model the fitness function. Examples include classical linear regression, splines, neural networks, Kriging and support vector regression. This paper specifically draws attention to the fact that assessing model accuracy is a crucial aspect in the meta-modeling framework. Resampling strategies such as cross-validation, subsampling, bootstrapping, and nested resampling are prominent methods for model validation and are systematically discussed with respect to possible pitfalls, shortcomings, and specific features. A survey of meta-modeling techniques within evolutionary optimization is provided. In addition, practical examples illustrating some of the pitfalls associated with model selection and performance assessment are presented. Finally, recommendations are given for choosing a model validation technique for a particular setting.

Homogene Approximation der Paretofront bei mehrkriteriellen Kontrollproblemen - Rudolph, G; Trautmann, Heike; Schütze, O (at-Automatisierungstechnik)
Es werden mehrkriterielle evolutio-näre Algorithmen (EMOA) für zwei- und höherdimensio-nale Probleme vorgestellt, die gleichmäßig verteilte Lö-sungen entlang der wahren Paretofront generieren. Diesist insbesondere wichtig im Kontext mehrkriterieller Kon-trollprobleme. Die Methodik beruht auf der Minimierungdes gemittelten Hausdorff-Abstandes in Bezug aufdie Paretofront. Die EMOA-Varianten werden vergleichendzu aktuellen Verfahren auf Benchmarkproblemen getestet.

Reduced dual task interference in multiple repeated dual-task tests: Automatization or task integration - Agethen, Manfred; Krause, Daniel (Current Research in Motor Control)

The Subject as Moral Person. On Husserl’s Late Reflections Concerning the Concept of Personhood - Luft, Sebastian (Investigating Subjectivity)

Max Schulze und Tobias Brembeck: Strom wechseln - Schulze, Max (Parkhaus)

Group Velocity - Schulze, Max (Zeitgenossenschaft)

Friedrich-Vordemberge-Stipendium für Bildende Kunst der Stadt Köln 2012 - Schulze, Max
Katalog zur Ausstellung im BBK Köln vom 31.10. - 25.11.2012

Frank Mehnert - Gretz, Daniela (Stefan George und sein Kreis. Ein Handbuch)

Von der mannigfaltigen Bedeutung der Reduktion nach Husserl - Luft, Sebastian (Phänomenologische Forschungen)
This paper takes a renewed look at Husserl’s method of the phenomenological reduction. It interprets “the reduction” as shorthand for the meaning of Husserl’s entire phenomenology in its mature stage. In the same way, the method of reduction might have different manners of execution but they are nevertheless guided by a common intent. The text takes its starting point by considering the different metaphors Husserl uses – the “flatland creatures” and the reduction as akin to a religious conversion – and spells out their implications, which lead me to consider their metaphilosophical significance. In this way, this article attempts a metaphilosophical reading of the meaning of the reduction in Husserl, which is equal to considering the meaning philosophy has for Husserl in the most general terms. In this way, some unorthodox reflections are carried out that shed new light on central phenomenological concepts, such as vidence and eidetic variation, phenomenology as a form of transcendental idealism, and the notorious problem of the lifeworld. In this way, Husserl’s phenomenology is interpreted as a peculiar representative of Enlightenment philosophy that restitutes a special notion of responsibility.
Keywords: General Medicine

Determinants of different types of born globals - Baum, Matthias; Schwens, C.; Kabst, Rüdiger (Handbook of Research on Born Globals)

Determinants of different types of born globals - Baum, Matthias; Schwens, C.; Kabst, Rüdiger (Handbook of Research on Born Globals)

“Why am I in this World?” Attitudes, Methods und Examples of Theologizing and Philosophizing with Children - Kammeyer, Katharina (Powerful Learning Environments and Theologizing and Philosophizing with Children)

Theologisieren in heterogenen Lerngruppen. Empirische Einsichten in Perspektiven von Lehrkräften und konzeptionelle Überlegungen - Kammeyer, Katharina (heologisieren mit Jugendlichen - ein Programm für Schule und Kirche)

Kindheitsforschung und Kindertheologie. Ein kindertheologischer Blick auf Beiträge soziologischer Kindheitsforschung - Kammeyer, Katharina (Zeitschrift für Religionspädagogik)

Allen Sternen wurde ihre Bahn gegeben... Sieht Gott auch für mich voraus? Zugänge zur Providentia Dei über die Josefsgeschichte - Kammeyer, Katharina; Benz, Sabine (Entwurf. Religionspädagogische Mitteilungen. Themenheft: Providentia Dei)

Anerkennung erfahren und geben lernen. Sonderpädagogische Überlegungen zu einer Pädagogik der Vielfalt - Kammeyer, Katharina (Glaube und Lernen. Themenheft: Inklusion)

Wie findest du, was Gott in der Geschichte tut? Gespräche und Spiele zu Gottes Zorn und Bund in der Noah-Geschichte - Kammeyer, Katharina (Grundschule Religion. Themenheft: Die dunklen Seiten Gottes)

Das Buch der Symbole. Auf Entdeckungsreise durch die Welt der Religion - Kammeyer, Katharina; Menzel, Gesa; Burggraf, Veronika; Hannecken, Kathrin; Kleinschmidt, Nadine („Gott hat das in Auftrag gegeben“. Mit Kindern über Schöpfung und Weltentstehung nachdenken.Jahrbuch für Kindertheologie,)

Children and the Theologians. Clearing the Way for Grace - Kammeyer, Katharina (Journal for the Study of Marriage & Spirituality)

Gehörter Tanz, gedachte Körper. Charles Mingus’ Jazzalbum 'The Black Saint and the Sinner Lady' (1963) - Münzmay, Andreas (Bewegungen zwischen Hören und Sehen: Denkbewegungen über Bewegungskünste)
Charles Mingus' "The Black Saint and the Sinner Lady" aus dem Jahre 1963 gehört zu den zentralen Werken des großformalen Jazz. Der Beitrag fragt zunächst nach den methodischen Implikationen der der musikhistorischen Quellensorte 'Jazzschallplatte' und plädiert für einen philologisch sorgsamen und sämtliche Dimensionen einer solchen Werkpublikation, vom medial gespeicherten Klangereignis bis zu den Paratexten, berücksichtigenden Zugriff. Von einer solcherart mehrdimensionalen 'Lektüre' der Schallplatte ausgehend wird der Versuch unternommen, die gängige pauschale Einschätzung des Albums als 'Tanzsuite' so weit wie möglich auszudifferenzieren. Was versteht Mingus unter "Ethnic Folk Dance Music"? Welchen Stellenwert haben Tanz und Körper in Mingus' ästhetisch-politischem Denken? Welche Vorstellungen von Tanz, Körper und Bewegung sollen evoziert werden, wenn Mingus die Tracks mit Überschriften wie beispielsweise „Duet Solo Dancers“ versieht? Entscheidend ist zum einen, dass Mingus die Großform von "The Black Saint and the Sinner Lady" weitgehend nach den eigentlichen Aufnahmesitzungen mittels tontechnischer Montageverfahren hergestellt hat; es handelt sich also gerade nicht um eine 'spontan' erimprovisierte Form. Zum anderen ist sein Interesse an zeitgenössischen amerikanischen Tanzavantgarden, und insbesondere an der tänzerisch-politischen Avantgardekunst der Katherine Dunham, mehrfach belegbar. So wird in der Zusammenschau von Musik und Kontext deutlich, dass "The Black Saint and the Sinner Lady" zwar nie konkret als Ballettmusik gedacht gewesen sein dürfte, aber wie kaum ein zweites Werk ein progressives ästhetisches Programm verfolgte, das - in bemerkenswerter Opposition zu anderen Strömungen der Jazzavantgarde um 1960 - nichts Geringeres als die Wiedergewinnung der Kategorien Tanz und Körper für den Jazz zum Ziel hatte.

What Drives WTP for Energy Efficiency When Moving? Evidence from a Germany-Wide Household Survey - Kesternich, Martin

Local Search and the Traveling Salesman Problem: A Feature-Based Characterization of Problem Hardness - Mersmann, Olaf; Bischl, Bernd; Bossek, Jakob; Trautmann, Heike; Wagner, Markus; Neumann, Frank (Revised Selected Papers of the 6th International Conference on Learning and Intelligent Optimization - Volume 7219)
With this paper we contribute to the understanding of the success of 2-opt based local search algorithms for solving the traveling salesman problem TSP. Although 2-opt is widely used in practice, it is hard to understand its success from a theoretical perspective. We take a statistical approach and examine the features of TSP instances that make the problem either hard or easy to solve. As a measure of problem difficulty for 2-opt we use the approximation ratio that it achieves on a given instance. Our investigations point out important features that make TSP instances hard or easy to be approximated by 2-opt.
Keywords: 2-opt; Classification; Feature Selection; MARS; TSP

Local Search and the Traveling Salesman Problem: A Feature-Based Characterization of Problem Hardness - Mersmann, Olaf; Bischl, Bernd; Bossek, Jakob; Trautmann, Heike; Wagner, Markus; Neumann, Frank (Learning and Intelligent Optimization)
With this paper we contribute to the understanding of the success of 2-opt based local search algorithms for solving the traveling salesman problem (TSP). Although 2-opt is widely used in practice, it is hard to understand its success from a theoretical perspective. We take a statistical approach and examine the features of TSP instances that make the problem either hard or easy to solve. As a measure of problem difficulty for 2-opt we use the approximation ratio that it achieves on a given instance. Our investigations point out important features that make TSP instances hard or easy to be approximated by 2-opt.

Der Club „Gleis 22". 25 Jahre andere Räume, andere Musiken, Kommunikation und Kreativität. - Jacke, Christoph (GLEIS 22 - Fünfundzwanzig Jahre Konzerte.)

Musik im Internet. Entwicklungen, Trends und Perspektiven. - Jacke, Christoph; Ahlers, Michael

Populärkultur. - Jacke, Christoph (Das Lexikon der Filmbegriffe.)

Kritische Theorie. - Jacke, Christoph (Das Lexikon der Filmbegriffe.)

Cultural Studies. - Jacke, Christoph (Das Lexikon der Filmbegriffe.)

Popmusik. - Jacke, Christoph (Das Lexikon der Filmbegriffe.)

Das Stück „Wanabni" der Palästinenserin Kamilya Jubran und des Schweizers Werner Hasler im multilokalen Hörtest. Eine multiperspektivische Analyse. - Jacke, Christoph; Burkhalter, Thomas; Passaro, Sandra (Black Box Pop. Analysen populärer Musik.)

Let's stick together! Popkulturforschung(en) in Deutschland als Projekt zwischen Unübersichtlichkeit und Formierung. - Jacke, Christoph; Kleiner, Marcus S. (Methoden der Populärkulturforschung. Interdisziplinäre Perspektiven auf Film, Fernsehen, Musik, Internet und Computerspiele.)

Impulse 2. Texte und Bilder zur Kunstvermittlung. Documenta 13 (2012): Kunstvermittlung und ihr Gegenüber.

Gehörter Tanz, gedachte Körper - Münzmay, Andreas (Bewegungen zwischen Hören und Sehen: Denkbewegungen über Bewegungskünste)

Telleranalysen: Molekularküche zwischen Werkstatt, Atelier und Labor./Plate Analysis: Molecular Gastronmy between Workshop, Studio and Laboratory. - Autsch, Sabiene (Atelier + Küche = Labore der Sinne (Publikation anlässlich der gleichnamigen Ausstellung, 12. Mai - 16. September 2012))

Nach der Bilderflut. Ästhetisches Handeln von Jugendlichen

BildGeschichte. Facetten der Bildkompetenz

Zwischen »Spacemaker« und gebautem Raum. Beobachtungen zum rezeptiven und gestalterisch-praktischen Umgang mit alltäglichen Räumen im Kunstunterricht - Pauls, Karina (Nach der Bilderflut. Ästhetisches Handeln von Jugendlichen)

BildGeschichte im Kunstunterricht am Beispiel einer gestalterischen und rezeptiven Auseinandersetzung mit Porträts in einem Grundkurs der Jahrgangsstufe 12 - Pauls, Karina (BildGeschichte. Facetten der Bildkompetenz)

Agentensysteme zur Kooperations- und Kollaborationsunterstützung - Wolff, Jens
Inhaltlich unveränderte Neuauflage. Der tägliche Informationsbedarf eines Menschen wird in Zukunft in allen Bereichen steigen und in digitalisierter Form aus den Telekommunikations netzwerken bezogen werden. Ohne geeignete Werkzeuge ist die Bewältigung dieser großen Menge an Informationen nicht möglich. Diverse Browser oder Suchmaschinen zählen zur ersten Generation solcher Werkzeuge. Eine neue Kategorie dieser Werkzeuge der Informationsgesellschaft bilden die so genannten intelligenten Softwareagenten . Sie erledigen im Auftrag des Benutzers selbstständig Aufgaben in der mittlerweile stark vernetzten Welt. Auch wenn in den vergangenen Jahren solche intelligenten Softwareagenten häufig Gegenstand von Spekulationen waren und nicht selten für Aufsehen sorgten, werden Effizienz und Effektivität entscheiden, ob es gelingt, die Potenziale der intelligenten Softwareagenten zu nutzen. Dadurch kann eine enorme Effizienzsteigerung erzielt werden. Die Agentensysteme bieten somit eine sehr gute Möglichkeit, Anwendungen und Dienste zu personalisieren und kommen dadurch den Präferenzen, Zielen und Wünschen der Anwender entgegen. Nicht der Mensch soll sich der Maschine anpassen, sondern umgekehrt die Maschine dem Menschen.

Rezension: Sabine Grosser: Kunst und Erinnerungskultur Sri Lankas im Kontext kultureller Globalisierung. [= Kunst und Kulturwissenschaft in der Gegenwart. Hg. v. Doris Schuhmacher-Chilla-Bd. 3]; Oberhausen (Athena Verlag) 2010; zahlreiche SW-Abb; 532 Seiten (mit umfassendem Bild- und Materialanteil. - Autsch, Sabiene (BDK-Mitteilungen)

Transport- und Bestellmengenplanung in Supply Chains - Harborth, Oliver (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand -)

Financial Chain Management als Koordinationsinstrument für Investitionsprojekte in Supply Chains - Heitmann, Ingmar (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand -)

Segmentspezifische und multikriterielle Bewertung von Standorten international agierender Unternehmen - Koch, Christian

Value Based Supply Chain Management (VBSCM) - Opitz, Oliver (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand)

Value Based Supply Chain Management (VBSCM) - Faupel, Christian (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand)

Philosophie trifft Politik. Von der Aktualität der Übungen im politischen Denken Hannah Arendts - Robaszkiewicz, Maria Anna (Zeitschrift für Didaktik der Philosophie und Ethik)

The Bright and Dark Side of Endowed Status in Hierarchical Loyalty Programs - Eggert, A.; Garnefeld, I.; Steinhoff, Lena (2012 AMA Summer Marketing Educators’ Conference Proceedings, Chicago)